O que educadores brasileiros pensam sobre o consumo de álcool e outras drogas? Um estudo panorâmico nacional - Borges, Alessandra Mieko Hamasaki [UNIFESP] (2019)
This dissertation is the result of a national survey on the perceptions and knowledge that educators at all levels of education have about alcohol and drug use. The research sought to interrelate and compare the data on the perceptions of educators with personal use or not and various aspects such as knowledge about the subject, courses, prejudices, fears, conceptions about legalization and decriminalization. The school institution is a privileged space for the development of programs for the prevention of alcohol and drug use, however Education does not seem to have made a commitment to the development of these actions and health promotion. Thus, due to the importance of the theme this qualitative study was developed and had the participation of 1132 educators who were invited to participate through social media and email. The research instrument used was a questionnaire prepared by the authors, consisting of 37 questions of sociodemographic, professional, perceptions about the use and prevention of alcohol and other drugs, and personal use. The survey was conducted through the online platform Surveymonkey and the questionnaire was launched in April 2018 and closed for data collection in October of the same year. For data analysis, the statistical program Statistical Package for Social Sciences (SPSS) was used. From the collected data we can observe that most educators claim to have taken prevention courses, however, the perceptions of the educators regarding some issues have divergent opinions when compared to the group of educators who use some kind of substance and those who never tried it. However, the opinion between the educators who took the course and those who did not are quite similar. Thus, we conclude that demystifying the approach to alcohol and drug use urgently depends on effective public policies; projects that cater to the specific public of each community and especially encourage the initial and continuing quality education for educators to act as prevention agents, without fears, prejudices or misperceptions.